Synthesis and crystal structure of cadmium(II) dichloroaquasalicylidenesemicarbazone - Panchenko, Tetiana; Evseeva, Maria; Ranskiy, Anatoliy; Baumer, Vyacheslav; Gordienko, Olga (Publishing House of Lviv Polytechnic National University, 2016)
Cadmium(II) complex with salicyl aldehyde semicarbozone (Н2L) has been synthesized. Based on elemental analysis and IR spectroscopy its composition – [Cd×Н2L×H2O×Cl2] – has been established. The complex crystal structure has been examined using XRD analysis. The coordination polyhedron of cadmium atom is a distorted octahedron, where two cis-positions are occupied by oxygen atoms of water molecule and carbamide fragment of H2L molecule, other positions are occupied by chlorine atoms. At the same time two edges of octahedron are combined with adjoined octahedrons and form endless zigzag chains of octahedrons in the structure along the crystallographic axis. H2L molecule is a planar one due to the presence of intramolecular hydrogen bond. Синтезовано комплекс кадмію(ІІ) із семикарбазоном саліцилового альдегіду (Н2L). За допомогою елементного аналізу та ІЧ-спектроскопії встановлено його склад – [Cd×Н2L×H2O×Cl2]. Кристалічну структуру комплексу досліджено за допомогою методу РСА. Встановлено, що координаційним поліедром атому кадмію є деформований октаедр, в якому два цис-положення займають атоми оксигену молекули води і карбамідного фрагменту молекули Н2L, решту положень займають атоми хлору. Показано, що два ребра октаедра є спільними із сусідніми октаедрами, за рахунок чого в структурі утворюються безкінечні зигзагоподібні ланцюги октаедрів уздовж кристалографічної осі. Молекула Н2L є плоскою завдяки наявності внутрішньомолекулярного водневого зв’язку.
Синтез і кристалічна структура дихлороаквасаліциліденсемикарбазон у кадмію(II)
Keywords: cadmium; salicylidenesemicarbazone; XRD; кадмій; саліциліденсемикарбазон; рентгеноструктурний аналіз